DESAIN DAN STRATEGI PEMBELAJARAN PENDIKAN AGAMA ISLAM PADA PERGURUAN TINGGI UMUM (PTU) DI KOTA MALANG - Kawakip, A. Nurul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
The paper explores the design and strategy of Islamic teaching (Pendidikan Agama Islam) which where implemented at Tribuana Tungga Dewi University of Malang. The university is consider as fairly a new university, established in 2001, located in the west of Malang. The findings of research are as follow: (1) the design of teaching is based on the actual topics that are based on students needs. (2) the strategies ofÂ teaching are applying various strategies such as moving class to some mosques, involving students in Islamic community surrounding of university, and reporting for daily religious activities.Â Keywords: Religious Activities, Moving Class, Involving In Society Sorrunding The University, and Actual Topics.